2008
DOI: 10.2106/jbjs.g.00265
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Procalcitonin and Cytokine Expression with Dehiscence of Wartime Extremity Wounds

Abstract: Effluent procalcitonin, IL-13, and RANTES protein levels as well as serum procalcitonin levels correlate with wound dehiscence following closure of severe open extremity wounds. These preliminary results indicate that effluent biomarker analysis may be an objective means of determining the timing of traumatic wound closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 50 publications
1
38
0
2
Order By: Relevance
“…Although we observed an association between wound failure and elevated serum ProCT and effluent IL-6 at the final débridement, the results should be interpreted with caution. Nevertheless, these results are similar to those of a previous study in which we observed that ProCT, measured in the serum and the effluent, and IL-13 were associated with wound failure in combat injuries [8]. These data suggest wound failure is associated with a persistent inflammatory state.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although we observed an association between wound failure and elevated serum ProCT and effluent IL-6 at the final débridement, the results should be interpreted with caution. Nevertheless, these results are similar to those of a previous study in which we observed that ProCT, measured in the serum and the effluent, and IL-13 were associated with wound failure in combat injuries [8]. These data suggest wound failure is associated with a persistent inflammatory state.…”
Section: Discussionsupporting
confidence: 91%
“…The massive physiologic insult caused by blast wounds produces a severe and poorly regulated systemic inflammatory response [8,11]. By measuring mediators of systemic and local inflammation, preliminary data suggest it may be possible to risk-stratify patients for HO and wound failure during the débridement process [6,8,11,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A treating clinician's decision to surgically close a wound is commonly based on subjective and somewhat arbitrary measures, such as the patient's general condition, the appearance of bones and soft tissues, and visual signs of infection or necrosis (65), which are poor indicators of the local inflammatory condition (66). This often has led to wound dehiscence and nonhealing wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the optimal timing for closure of these residual limbs is therefore difficult [3,5]. Given the large zones of injury and random pattern flaps often used for closure, potential spaces are created.…”
Section: Introductionmentioning
confidence: 99%